Study of the lifecycles of Si molds and the quality of their injection molding products - Yi, Jin (2014)
The durability of Si molds and the quality of their injection molding products depend on its surface characteristics and properties. Theoretically coatings will improve the properties and subsequently make the quality of their products better. This project investigated the effects of the coatings on the lifecycle of Si Mold and the quality of their plastic products. A series of five Si molds were coated with DLC films in different compositions using sputtering technique. These Si molds together with several uncoated molds were studied with Scanning Electron Microscopy (SEM), Contact Angle and Atomic Force Microscopy (AFM). It was found that the surface properties of the coated Si molds were better than the uncoated ones except the roughness. Design of experiment was conducted on the injection molding for further study and comparison of the uncoated and coated Si molds. Close lifecycles of uncoated and coated Si molds were obtained according to the injection molding results. Further testing was done to study the Si molds’ conditions after certain runs of injection molding and the quality of their products. With the testing results from Confocal Imaging Profiler, Talyscan and SEM, the surface quality of the products from coated Si molds was improved compared to those from uncoated Si molds. In summary, coatings on the Si mold really improve the surface properties and make their products much better.